Dispersion properties of arbitrary cross-section plasma-filled waveguide in a finite magnetic field - Shcherbinin, V.I.; Zaginaylov, G.I.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2013)
The study presents a universal approach to solving a boundary value problem for waveguide of arbitrary crosssection with longitudinally magnetized plasma filling. The approach utilizes representation of longitudinal fields by infinite scalar series. The dispersion equation of magnetized plasma-filled waveguide of arbitrary cross-section is obtained. As examples, numerical results for three types of plasma-filled waveguides (circular, coaxial and rectangular) are presented. Their dispersion properties, as well as convergence of numerical results, are investigated numerically. The validity of the results is verified by comparison with known data.